2019
DOI: 10.1002/ana.25426
|View full text |Cite
|
Sign up to set email alerts
|

Variation in SIPA1L2 is correlated with phenotype modification in Charcot– Marie– Tooth disease type 1A

Abstract: Objective: Genetic modifiers in rare disease have long been suspected to contribute to the considerable variance in disease expression, including Charcot-Marie-Tooth disease type 1A (CMT1A). To address this question, the Inherited Neuropathy Consortium collected a large standardized sample of such rare CMT1A patients over a period of 8 years. CMT1A is caused in most patients by a uniformly sized 1.5 Mb duplication event involving the gene PMP22. Methods: We genotyped DNA samples from 971 CMT1A patients on Illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 51 publications
2
34
0
Order By: Relevance
“…This is also true for different variants of the amino acid adjacent to the p.Asp411Gly variant we have reported here, where p.Glu412Gly causes both demyelinating CMT1D 12 and axonal CMT 14 , and p.Glu412Lys causes DSN 35 . Given these observations, it is possible that additional genetic factors exist which modify the phenotype of EGR2 variant, such as those recently reported for CMT1A 37 .…”
Section: Discussionmentioning
confidence: 92%
“…This is also true for different variants of the amino acid adjacent to the p.Asp411Gly variant we have reported here, where p.Glu412Gly causes both demyelinating CMT1D 12 and axonal CMT 14 , and p.Glu412Lys causes DSN 35 . Given these observations, it is possible that additional genetic factors exist which modify the phenotype of EGR2 variant, such as those recently reported for CMT1A 37 .…”
Section: Discussionmentioning
confidence: 92%
“…Finally, RT induced gene expression of both SIPA1L (signal-induced proliferation associated 1 like)2 and LOXHD (lipoxygenase homology domains)1, genomic variants in which are associated with PD in previous studies (Safaralizadeh et al, 2016;Wang et al, 2016;Gaare et al, 2018;Tao et al, 2019). Presently, there is no available evidence of single-nucleotide polymorphisms in these genes contributing to differential expression in healthy skeletal muscle tissue.…”
Section: Genes Linked To Pd Pathologymentioning
confidence: 94%
“…Identifying genetic modifiers is challenging as it often requires large sample sizes, but this problem can be overcome with the use of extreme phenotype sampling (EPS)a technique that focuses on alleles that tend to associate with one phenotypic extreme rather than random sampling 49 . This approach was used in a well-designed genome-wide genotyping study on a large sample of 330 deeply phenotyped patients with CMT1A who were of European ancestry 50 . This study identified the SIPA1L2 gene as a genetic modifier of ankle dorsiflexion weakness, a hallmark feature of CMT.…”
Section: Whole-genome Sequencingmentioning
confidence: 99%